THE ROLE OF THE STATE MECHANISM IN BUILDING A MODERN LEGAL GOVERNMENT - Aminov Dalerjon Alisher-o’g’li; Qudratova Kumush Murodjon qizi (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article provides a comprehensive overview of the content of the concept of government mechanisms, previous theoretical analysis of national scientists in this regard, its organization, its functioning, especially the principle of division of power, the historical formation process of government mechanisms, and its key participants and proposals for addressing deficiencies and problems in the process of operation